How Digital Cats Tame Ideology: the Cat Content of Soviet Nostalgia as an Ideological Mediator - Sophia V. Tikhonova (Галактика медиа: журнал медиа исследований)
The article deals with the mechanics of broadcasting ideology through online user content, dedicated to domestic cats. The author believes that digital culture is changing the logic of the relationship between written and oral, long and short genres of objectification of ideology in mass consciousness. It ensures the presence of complex long ideological genres of Modernity in the media space, reinforcing it with a wide “protective belt” of microformats characteristic of entertainment content. The most typical type of the latter is cat content, which is understood as a form of social reflection that sets a cliched reaction to a media message through the image of a digital cat. The purpose of the article is to analyze the use of political ideologies in the context of Soviet nostalgia. The author examines the polar versions of the visualization of Soviet nostalgia in the context using the example of Vasya Lozhkin’s cats and the VK public “Cats for Communism”. The semantic multilayering of Vasya Lozhkin’s paintings is ensured by the fluidity and interchangeability of zoo- and anthropomorphic features of the characters and the ease of their ethical (de)evolution. The transition of cats to the red side is shown as a rather late phenomenon of digital culture, inscribed in the period of the last five years. Digital cats dearchaize communist ideology by associating it with digital fashion. In general, digital cats disassemble ideological narratives into micro-rhythms and creolize them, performing the function of a mediator forwarding the actualized old ideologies into the digital media space.